The comparative analysis of Sino-Japanese football policies from the perspective of policy instruments - Chuanmin Zhang; Zanying Hu; Huqiang Wei; Mei Peng; Fei Gao (PLoS ONE, 2026)
Football development depends heavily on strong policy support, rendering policy analysis and evaluation of significant practical importance. This study uses Nvivo11 software and the PMC index model to conduct a quantitative comparative analysis of 31 Sino-Japanese football policy texts, focusing on policy instruments, content characteristics, and overall quality. The findings reveal that both countries prioritize football development, social participation, and club construction; China emphasizes campus football, while Japan focuses on elite player development and league performance. PMC evaluation indicates that Chinese policies score higher in system design and institutional capacity, whereas Japan performs better in implementation clarity and community linkage. Both countries share shortcomings in insufficient policy clarity and vague long-term competitive goals. The research results provide empirical evidence for the optimization of Chinese football policies and a reference for drawing on international experience.